Larval development of Petrolisthes tuberculatus (Guérin, 1835) (Decapoda, Anomura, Porcellanidae) reared in laboratory - Gonzalez-Canales, Maria Eugenia; Cuesta, Jose A.; González-Gordillo, Juan Ignacio (Zootaxa, 2019)
The complete larval development of Petrolisthes tuberculatus (including two zoeal stages and the megalopa) is described and illustrated in detail for the first time, based on laboratory-reared material. In order to allow the differentiation of specimens from plankton samples, the larval stages of P. tuberculatus are compared with those known for other porcellanid crabs from Chilean waters (Allopetrolisthes angulosus, Petrolisthes granulosus, P. laevigatus and P. violaceus). As expected, this comparison lead to the inclusion of P. tuberculatus within the “sección Porcellanina” together with the other Chilean species of porcellanids.